Utilization of Educational Technology in The Learning Process in The Sub-District of Tebas, Sambas Regency - Warneri; Okianna (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
This study aims to determine the use of educational technology in the learning process for educators in Tebas District, Sambas Regency, the theoretical use of research to contribute to the development and use of educational technology and practically to be able to apply the development of educational technology today. The variables in this study are Utilization of educational technology in the learning process